Associations of macrosomia with sociodemographic, anthropometric, lifestyle factors and perinatal outcomes in Southwest Nigeria - Ikeola A. Adeoye; Joshua I. Fakorede; Mobolaji M. Salawu; Kofoworola I. Adediran (BMC Pediatrics)
Abstract Background Currently, macrosomia contributes to maternal and neonatal morbidity and mortality in low—and middle-income countries because of changes in maternal lifestyle. Reliable data are needed for its prevention, early detection, and management. This study assessed the associations between sociodemographic, anthropometric, maternal lifestyle, perinatal outcomes, and macrosomia in Southwest Nigeria. Methods We used the Ibadan Pregnancy Cohort Study (IbPCS) data, which investigated maternal obesity, lifestyle factors and the associated pregnancy outcomes among 1745 antenatal care attendees in Southwest Nigeria. This study examined the 1200 women who were not lost to follow-up, had health facility deliveries and the infants’ birthweight records. Outcome variables were macrosomia (birthweight ≥ 4 kg) and perinatal outcomes. Explanatory variables were sociodemographic, anthropometric, and maternal lifestyle factors. Maternal blood glucose and lipids were assessed between 24 and 28 weeks’ gestation. Bivariate and multiple logistic and Poisson regression analyses examined the associations at a 5% level of statistical significance. Results The prevalence of macrosomia was 72 (6%) [95% CI: 4.66–7.35]. On bivariate analysis parity (p = 0.009), maternal age (p = 0.012), history of macrosomia (0.021), consumption of protein-rich diets with non-alcoholic beverages (p = 0.021), sex of infants (p = 0.018), and engagement in physical activity (p = 0.036) were significantly associated with macrosomia. The mean maternal glucose levels were significantly higher among mothers with macrosomic babies compared with those without macrosomia: FPG: 4.72 ± 2.32 vs. 4.32 ± 0.9 mmol/l (p = 0.035), 1-hour plasma glucose: 8.80 ± 3.77 vs. 6.97 ± 1.93 mmol/l (p < 0.001), 2-hour plasma glucose: 7.16 ± 3.20 vs. 6.25 ± 1.73 mmol/l (p = 0.008). The predictors of macrosomia include a history of macrosomia [AOR = 2.057, 95% CI: 1.009–4.191), maternal obesity [AOR = 1.883, 95% CI: 1.027–3.451], and male infants [AOR = 1.847, 95% CI: 1.016–3.357) were more likely to have macrosomia compared to female infants. Furthermore, Emergency Cesarean section was a significant outcome of macrosomia [RR = 1.675, 95% CI: 1.068–2.627]. Conclusions Macrosomia was common among our study population. This study identified common modifiable risk factors for foetal macrosomia, its mechanistic pathways and suggested prevention and control strategies for macrosomia among pregnant women.